Effect of crucible design on crystalline perfection and the enhanced optical properties of benzimidazole single crystals grown by the vertical Bridgman technique. (18th January 2013) - Riscob, B.; Vijayan, N.; Shakir, Mohd; Wahab, M. A.; Bhagavannarayana, G.
Abstract : Good quality benzimidazole (BMZ) single crystals were successfully grown by the vertical Bridgman technique (VBT). The unavoidable thermal‐induced structural grain boundaries formed in the normal VBT growth of these crystals with low melting point were controlled by using a double‐wall ampoule. The grown single crystals were subjected to high‐resolution X‐ray diffraction to assess their crystallinity. The enhancement of optical properties due to the improvement in crystalline perfection is also reported.